1987
DOI: 10.1084/jem.165.3.693
|View full text |Cite
|
Sign up to set email alerts
|

The human natural anti-Gal IgG. III. The subtlety of immune tolerance in man as demonstrated by crossreactivity between natural anti-Gal and anti-B antibodies.

Abstract: A well-defined antigen/antibody system was used to evaluate the effect of immune tolerance on the spectrum of specificities of natural antibodies. The antibody used in this study, anti-Gal, is a naturally occurring, polyclonal IgG that constitutes 1% of the circulating IgG in humans. We have previously shown that anti-Gal, purified from AB sera, specifically interacts with glycosphingolipids bearing a Gal alpha 1----3Gal epitope, but not with the closely related B antigen in which the penultimate galactose of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
125
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 202 publications
(131 citation statements)
references
References 33 publications
(35 reference statements)
6
125
0
Order By: Relevance
“…Moreover, a large proportion of anti-blood group antibodies are in fact anti-Gal antibodies that bind to the a-gal epitope that serves as the core structure for these blood group antigens. 12,41,42 ABO incompatibility is presently one of the major limiting factors in transplantation of allografts in humans. [43][44][45][46] By using autologous lymphocytes transduced with adenovirus containing A or B transferase gene, 47 one may induce tolerance similar to that observed with AdaGT transduced lymphocytes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, a large proportion of anti-blood group antibodies are in fact anti-Gal antibodies that bind to the a-gal epitope that serves as the core structure for these blood group antigens. 12,41,42 ABO incompatibility is presently one of the major limiting factors in transplantation of allografts in humans. [43][44][45][46] By using autologous lymphocytes transduced with adenovirus containing A or B transferase gene, 47 one may induce tolerance similar to that observed with AdaGT transduced lymphocytes.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] The a-gal epitope is a carbohydrate antigen naturally expressed on cells of nonprimate mammals and New World monkeys and is absent in humans, apes and Old World monkeys, all of which produce large amounts of the natural anti-Gal antibody that interacts specifically with this epitope. [8][9][10][11][12] Binding of the natural anti-Gal antibody to a-gal epitopes on pig xenografts induces rapid rejection of such grafts in humans or monkeys. [13][14][15][16] Wild-type (WT) mice express an abundance of a-gal epitopes, similar to other nonprimate mammals.…”
Section: Introductionmentioning
confidence: 99%
“…30 Anti-Gal interacts specifically with the a-gal epitope (Gala1-3Galb1-4GlcNAc-R), a carbohydrate epitope abundantly produced on glycoproteins and glycolipids of non-primate mammals and New World monkeys by the glycosylation enzyme a1,3galactosyl-transferase (a1,3GT). [31][32][33][34] We and others found that the a-gal epitope is absent, however, in Old World monkeys, apes and humans, because of evolutionary inactivation of the a1,3GT gene in ancestral Old World primates. [34][35][36][37] As an outcome of these evolutionary differences, anti-Gal functions in vivo as a major barrier for xenotransplantation of pig organs in humans, as its binding to a-gal epitopes on pig xenograft cells induces rapid rejection of the graft.…”
mentioning
confidence: 99%
“…Although antiGal is present in large amounts in humans it interacts with a very high specificity with a carbohydrate antigen (Ag) called the -gal epitope (Gal1-3Gal1-4GlcNAc-R) on glycolipids and glycoproteins (Galili et al, 1985;1987a). Anti-Gal is produced in humans throughout life as a result of continuous antigenic stimulation by gastrointestinal bacteria with cell wall carbohydrate Ags that have a structure similar to the -gal epitope (Galili et al 1988a).…”
Section: Introductionmentioning
confidence: 99%
“…In individuals with blood type A and O, >80% of anti-blood group B activity is in fact by anti-Gal Abs that are capable of binding to -gal epitopes despite of the branching fucose, as in blood group B Ag (i.e. Gal1-3(Fuc1-2)Gal1-4GlcNAc-R) (Galili et al, 1987a;McMorrow et al, 1997). However, in blood group B and AB individuals, anti-Gal exclusively interacts with the -gal epitope and not with other carbohydrate structures.…”
Section: Introductionmentioning
confidence: 99%